1996
DOI: 10.1097/00007890-199601150-00030
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide Studies in Intestinal Transplantation

Abstract: Three patients who received intestinal allografts were studied using two distinct radionuclide investigations. In the first, 111In or 99mTc-labeled leukocyte scanning was performed to assist in the diagnosis of rejection. It was able to demonstrate the occurrence of rejection in the transplanted intestine, and the response to antirejection therapy. In 1 case, the abnormality on the scan preceded the histological confirmation of rejection. The second technique studied mucosal integrity by serial 51Cr-EDTA/14C-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Bone-marrow derived MSCs were also imaged in the brains of rats with traumatic brain injury . Finally, radiolabeled leukocytes have been used preclinically to evaluate graft rejection as an alternative to biopsies, ,, showing for example that 18 F-labeled lymphocytes could distinguish between allograft rejection and other causes of organ-specific toxicity …”
Section: Applications and Clinical Translation Of Cell Trackingmentioning
confidence: 99%
“…Bone-marrow derived MSCs were also imaged in the brains of rats with traumatic brain injury . Finally, radiolabeled leukocytes have been used preclinically to evaluate graft rejection as an alternative to biopsies, ,, showing for example that 18 F-labeled lymphocytes could distinguish between allograft rejection and other causes of organ-specific toxicity …”
Section: Applications and Clinical Translation Of Cell Trackingmentioning
confidence: 99%
“…Isolauri et al (13,14) have shown that intestinal permeability increases in patients with acute viral gastroenteritis. Graft rejection appears to impair intestinal mucosal barrier function, which recovers very slowly after treatment (15). Patient 3 did have Rotavirus enteritis before the onset of food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the development of numerous diagnostic methods, which have not been validated in human intestinal transplantation or have limited value ( 8, 9). Apart from intestinal permeability studies ( 10), which are not fully reliable, and, more recently, scintigraphic scanning using 99 Technetium‐labelled leucocytes ( 11), there are no simple tests reflecting the state and/or function of the entire graft. Hence, regular biopsies of the proximal and distal ends of the graft for histologic or immunohistochemical analysis, are required ( 12–14).…”
Section: Complications After Intestinal Transplantationmentioning
confidence: 99%